Modern Approach To The Using Of Informations Technologies For Organization Educational Process (Journal of Information Technologies in Education (ITE), 2009)
The system of creation of the distance learning course are proposed. with the controlled from distance access for independent preparation; this computer system does not require knowledges of information technologies from teachers.
Keywords: distance learning; e-book; e-learning; knowledge’s testing